Contact-Area-Changeable CMP Conditioning for Enhancing Pad Lifetime - Jungyu Son; Hyunseop Lee (Applied Sciences, 2021)
Chemical–mechanical polishing (CMP) is a process that planarizes semiconductor surfaces and is essential for the manufacture of highly integrated devices. In CMP, pad conditioning using a disk with diamond grit is adopted to maintain the surface roughness of the polishing pad and remove polishing debris. However, uneven pad wear by conditioning is unavoidable in CMP. In this study, we propose a contact-area-changeable conditioning system and utilize it to conduct a preliminary study for improving pad lifetime. Using the conventional conditioning method (Case I), the material removal rate (MRR) decreased rapidly after 12 h of conditioning and the within-wafer non-uniformity (WIWNU) increased. However, the results of conditioning experiments show that when using a contact-area-changeable conditioning system, uniform pad wear can be obtained in the wafer–pad contact area and the pad lifetime can be extended to more than 20 h. Finally, the newly proposed conditioning system in this study may improve the CMP pad lifetime.